Ekspresi produk gen laten virus epstein-barr pada karsinoma sel skuamosa rongga mulut (The expressions of latent gene product of epstein-barr virus in oral squamous cell carcinoma) - Theresia Indah Budhy S (Dental Journal (Majalah Kedokteran Gigi), 2005)
Squamous cell carcinoma (SCC) is a type of cancer often found in oral cavity and the area of head and neck at about 90%. Based on the geographical incidence oral SCC (OSCC) has many types of different emerging. This case probably has connection with ethnic group, habit and social and economical condition. In East Java, the incidence is about 2.64% and it increases every year. The virus is known as one of the main factors that result in this disease. Epstein-Barr virus (EBV) has potential capability of carcinogenesis. EBV is the family of herpesviridae that can infect cell through the linking of CD 21 receptor of the epithel with glycol protein 350/220 of the virus capsule. After primary infection, the virus will form latent-gene in human cell. Periodically, the latent-gene product can disturb proliferation and apoptotic regulator. In Indonesia, the expression of EBV latent geneproduct in the OSCC has not been reported yet. This study wanted to know the expression of EBV latent gene product found in the OSCC. This study found 25 cases of OSCC in which 17 were infected by EBV. Detection of EBV infection could be done by insitu hybridization to identify RNA EBV (EBER). To find the expression of EBV latent gene product, immunohistochemical analysis was done. The conclusion was that the emerging of expression of EBV latent gene product in OSCC were latent membrane protein-1 (LMP-1), EBV nuclear antigen-1 (EBNA-1) and RNA EBV (EBER). They were 28.28%, 25.26% and 46.47%. It was suggested to do the following research on OSCC infected by EBV and the emerging of expression of EBV latent gene product with regulator gene of proliferation and apoptotic in OSCC.